Study on Securely Digitalizing Crime Records by using RSA Algorithm - Naik, M. Nagaraju; Kumar, S.Muni; Kumar, J.S. Ananda (International Journal of Computer Sciences and Engineering, 2025)
Crime Records are exists in Police Stations. Crime Records are enable to find crimes and their involved criminals. In the existing system they are using a FIR for maintain the crime and criminal details. It contain a less security and easy to perform fraud. The record has been updated manually every time. The main objective of this system is providing security to data, by using the RSA algorithm. It contain the two keys based security. In this, crime and involved criminal details are stored in database in the form of encrypted data. Criminal details such as (name, address, etc,) are stored in the Ciphertext format. So that we can speed up investigation process as soon as possible. Highly impossible to decrypt data who are unauthorized to access crime data. Through the using this system witnesses can easy to access and generate the reports. We can providing a security to witnesses data by using RSA algorithm. If any person performing misleading activities to on crime data they can’t access plain text and difficult to change cipher text to plain text.